Analysis of the responsible site for favipiravir resistance in RNA-dependent RNA polymerase of influenza virus A/PR/8/34 (H1N1) using site-directed mutagenesis - Komeno, Takashi; Furuta, Yousuke; Nakajima, Nozomi; Tani, Hideki; Morinaga, Yoshitomo (Antiviral Research, 2022)
Favipiravir (T-705, 6-fluoro-3-hydroxy-2-pyrazinecarboxamide) selectively and strongly inhibits the replication of influenza virus in vitro and in vivo. Favipiravir is converted to favipiravir-4-ribofuranosyl-5-triphosphate (favipiravir RTP) by intracellular enzymes and functions as a nucleotide analog to selectively inhibit RNA-dependent RNA polymerase (RdRP) of influenza virus. Our previous experiments failed in an attempt to obtain a favipiravir-resistant influenza virus in vitro using influenza virus A/PR/8/34(H1N1). Conversely, Goldhill et al. reported a favipiravir-resistant influenza virus generated by in vitro passage of influenza virus A/England/195/2009 (H1N1), an early isolate from the 2009 H1N1 pandemic (pdm09), in the presence of favipiravir with K229R mutation in PB1. This study focused on K229R mutation near the NTP cross-linked region in PB1 based on the above conflicting findings to confirm whether K229R mutation brings favipiravir resistance to influenza virus A/PR/8/34. Thirty PB1 mutants generated by site-directed mutagenesis of the NTP cross-linked region were evaluated using an influenza virus A/PR/8/34 replicon system. Among the 30 mutants, 10 possessed but 20 lost replicon activity. When susceptibility to favipiravir in 10 mutants was further assessed, the PB1 E491D mutant was five times more sensitive than the wild-type (WT), while only the PB1 K229R mutant was resistant to favipiravir. Results suggested that the evaluated region was essential for polymerase activity, and K229 mutation was responsible for polymerase inhibition of favipiravir in the influenza virus A/PR/8/34. Interestingly, the tested K229X series mutants entirely lost replicon activity, except for K229R. This suggested that the amino acid at position 229 in PB1 of influenza virus may play a pivotal role in polymerase activity. Moreover, this lysine residue is highly conserved among positive- and negative-sense single-stranded RNA viruses, in which favipiravir showed potent activity, suggesting that this mutation may determine the characterization of the in vitro broad-spectrum activity of favipiravir. Additionally, this mutation acquisition greatly influences the viral replication and the susceptibility to favipiravir.